Abundance, habitat use and food consumption of seabirds in the high-Arctic fjord ecosystem - Stempniewicz, Lech; Goc, Michał; Głuchowska, Marta; Kidawa, Dorota; Węsławski, Jan Marcin (Polar Biology, 2021)
Abstract To monitor the rapid changes occurring in Arctic ecosystems and predict their direction, basic information about the current number and structure of the main components of these systems is necessary. Using boat-based surveys, we studied the numbers and distribution of seabirds foraging in Hornsund (SW Spitsbergen) during three summer seasons. The average number of seabirds foraging concurrently in the whole fjord was estimated at 28,000. Little Auks Alle alle were the most numerous, followed by Northern Fulmars Fulmarus glacialis , Brünnich’s Guillemots Uria lomvia and Black-legged Kittiwakes Rissa tridactyla . The pelagic zone was exploited by some 75% of the birds. Their density was the highest (> 400 ind. km −2 ) in the tidewater glacier bays, where kittiwakes were predominant, and the lowest in the coastal glacier bays. The seabirds in Hornsund daily consumed c. 12.7 tons of food, i.e. c. 0.2% of the summer mesozooplankton and fish standing stocks available in the fjord. This food consisted primarily of copepods, amphipods and molluscs (c. 70%), whereas fish made up < 15%. More than 50% of this biomass was ingested by pursuit divers, while surface feeders took c. 29% and benthophages c. 13%. About three-quarters of the food biomass was taken from the pelagic zone. This paper describes, for the first time in quantitative terms, the structure and function of a seabird community foraging in an Arctic fjord. It also provides a baseline for future studies on climate-induced changes in the importance of seabirds in the Arctic food web.